2012
DOI: 10.1016/j.neurobiolaging.2011.09.015
|View full text |Cite
|
Sign up to set email alerts
|

DJ-1 and αSYN in LRRK2 CSF do not correlate with striatal dopaminergic function

Abstract: Previous studies demonstrated decreased levels of DJ-1 and α-synuclein (αSYN) in human cerebrospinal fluid (CSF) in patients with Parkinson’s disease (PD), but neither marker correlated with PD severity, raising the possibility that they may be excellent progression markers during early or preclinical phases of PD. Individuals carrying the leucine-rich repeat kinase 2 (LRRK2) gene mutation are at increased risk for PD, and the phenotype of LRRK2 patients is almost identical to sporadic PD. To determine whether… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
32
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 3 publications
(7 reference statements)
2
32
2
Order By: Relevance
“…In addition, a recent study by Shi et al (2012) described a lack of relation between the loss of striatal dopaminergic function, assessed by positron emission tomography (PET), and CSF α-synuclein levels, in asymptomatic carriers of mutations in the LRRK2 gene. CSF neurosin (a protease that degrades α-synuclein) levels have been found to be decreased (Wennström et al, 2013).…”
Section: Proteins Involved In the Pathogenesis Of Parkinson's Diseasementioning
confidence: 99%
“…In addition, a recent study by Shi et al (2012) described a lack of relation between the loss of striatal dopaminergic function, assessed by positron emission tomography (PET), and CSF α-synuclein levels, in asymptomatic carriers of mutations in the LRRK2 gene. CSF neurosin (a protease that degrades α-synuclein) levels have been found to be decreased (Wennström et al, 2013).…”
Section: Proteins Involved In the Pathogenesis Of Parkinson's Diseasementioning
confidence: 99%
“…In particular, reduced striatal dopamine function strongly correlates with reduced CSF Aβ proteins3 rather than CSF α-synuclein levels4 in these preclinical LRRK2 cases. In sporadic PD, many studies have shown correlations between reduced CSF Aβ and cognitive impairment and more rapid cognitive decline,5–8 particularly with deficits in verbal fluency which may have a motor component.…”
mentioning
confidence: 90%
“…Thus, a current major focus of early PD biomarker research is to identify biochemical marker candidates in the brain or body fluids, which might reflect the state of the disease. We have already investigated several potential cerebrospinal fluid (CSF) markers (known to be important in sporadic PD) in a cohort of symptomatic and asymptomatic subjects carrying one of the strongest risk factors for PD - the leucine rich repeat kinase 2 ( LRRK2 ) gene mutations, and identified that some CSF protein levels correlated with the progressive loss of striatal dopaminergic functions as determined by positron emission tomography (PET) [8, 9]. The emergence of several –omics techniques, including transcriptomics, proteomics and metabolomics, has also greatly enhanced our ability to identify novel pathways and potential biomarkers for PD [7, 10, 11].…”
Section: Introductionmentioning
confidence: 99%